2023
DOI: 10.1037/ser0000628
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of an intensive outpatient treatment program for posttraumatic stress disorder within the veterans health care administration.

Abstract: Trauma-focused treatments for posttraumatic stress disorder (PTSD), such as Prolonged Exposure (PE) therapy and Cognitive Processing Therapy (CPT), are effective and supported by various Clinical Practice Guidelines; however, drop-out rates for the treatments are as high as 40% within clinical programs. One promising solution is delivering the evidence-based psychotherapies (EBPs) three or more times per week within an intensive outpatient program (IOP) for PTSD. The present study examined the feasibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The most recent clinical research has demonstrated that PTSD recovery can be expedited and there are lower patient dropout rates when sessions are massed or compressed so that multiple sessions are administered over 1 week. [8][9][10][11][12] Providing these therapies in a massed format has shown to be as effective as when these therapies are provided weekly.…”
Section: Discussionmentioning
confidence: 99%
“…The most recent clinical research has demonstrated that PTSD recovery can be expedited and there are lower patient dropout rates when sessions are massed or compressed so that multiple sessions are administered over 1 week. [8][9][10][11][12] Providing these therapies in a massed format has shown to be as effective as when these therapies are provided weekly.…”
Section: Discussionmentioning
confidence: 99%
“…IOPs are intensive treatment programs which offer adjunctive interventions such as yoga and mindfulness classes, in addition to the primary EBPs [51,53,54]. Yamokoski et al [55] describe a clinic in which two intensive protocols were offered. The shorter option held five treatment days per week and took around two weeks to complete in total.…”
Section: Shortening the Duration Of Sessions And Protocolsmentioning
confidence: 99%
“…Group sessions were used primarily to support individual therapies, such as clarifying treatment rationales, progress reviews, or addressing any difficulties patients might be experiencing. Outside therapy sessions, patients also worked on homework assignments and/or presented to psychiatry appointments [55].…”
Section: Shortening the Duration Of Sessions And Protocolsmentioning
confidence: 99%
See 2 more Smart Citations